N-terminal pro-brain natriuretic peptide in essential arterial hypertension patients: antihypertensive therapy effects - A. S. Galyavich; E. R. Valiullina (Российский кардиологический журнал)
The authors studied N-terminal pro-brain natriuretic peptide (N-proBNP) role in 43 essential arterial hypertension (EAH) patients, as well as antihypertensive therapy effects on N-proBNP. N-proBNP levels were independent of gender or age. ACE inhibitor spirapril significantly decreased N-proBNP level, while calcium antagonist nifedipine and beta-adrenoblocker metoprolol did not affect it.